Feminism as a revolutionary theory - Alipbayev, A.; Byuzheyeva, B.; Balaubayeva, B.; Jaukasharova, G. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
This article discusses the issue of feminist theory. The novelty of the work lies in the analysis of this theory, taking into account the similarity of signs of its appearance in the theory of international relations with signs of a revolution according to the definitions of political science. Nowadays feminism theory is becoming conventional, and it is currently investigated and discussed widely in both social and political contexts. As a theory of international relations (IR), feminism criticizes traditional international relations theories, especially the world system made by realists. Unlike other theories that occurred as a response to realism, feminism can be distinguished with its «silence» for a long time. It is different from other theories in that it speaks for a half of the population, emerged «suddenly» and covered almost all aspects of life. Starting with struggle for basic human rights, feminism has expanded the range of issues covered both in political and social life. It cannot be denied that due to the limits to be involved in politics, women lived in the framework of regulations made by men. Surely, all IR theories do not agree with each other, especially in a number of issues such as driving forces of domestic and foreign policies states and other actors in international realm. However, all IR theories were made by men despite of the fact that about half of population of any state are women. Women had lived with the laws made by another half of population (men) for a long time, and they started to be involved in IR when limits in social life were mitigated or removed. There is one more phenomenon in politics, the emergence and development of which are similar to the revolution, the struggle of which usually appears when the victims get tired of the oppression of governors and authorities. In this article we consider the feminism theory as a revolution in IR and try to define their similarities with the help of analysis of revolution theories and historical stages of feminism.
Феминизм революциялық теория ретінде
Феминизм как революционная теория
Keywords: feminism; the feminism theory; revolution; international relations; gender; gender politics; gender issues